THE EFFECTIVENESS OF NATURAL GROWTH STIMULANTS IN THE CULTIVATION OF SEEDLINGS OF PICEA OBOVATA LEDEB. - Tatiana Vladimirovna Khurshkainen; Svetlana Karlenovna Stetsenko; Elena Mikhailovna Andreeva; Gennady Grigorievich Terekhov; Alexander Vasilievich Kutchin (Химия растительного сырья, 2021)
Picea obovata Ledeb. is a slow-growing in the early stages of growth type of coniferous trees. The use of growth stimulants in the cultivation of spruce seedlings can accelerate the production of standard planting material. The paper presents the results of research of plant growth regulators influence on spruce seedlings within three years of cultivation in forest nursery conditions. Before sowing seeds of spruce soak in solutions of biological-active preparations Verva and Verva-spruce, obtaining from Abies and Picea wood greenery extracts. The plants growth regulator Verva from Abies needles (operating substance – triterpenic acids) is applied in plant growing at cultivation agricultural and commercial crops. Operating substance of a preparation Verva-spruce used for protection of agricultural plants from diseases, are phenolic compounds of Picea wood greenery possessing fungicidal and insecticidal activity.It is established that spruce seedlings processed before sowing by bio-preparation had higher parameters of growth (seedling height, diameter of seedling tree at root neck) in comparison with control plants within three years of cultivation in conditions of forest nursery. Three-year spruce seedlings which have been grown up with use of growth stimulators Verva and Verva-spruce exceeded control on 20–30% on height and on 19–20% on seedling tree thickness. Bio-preparations Verva and Verva-spruce can be recommended for application in forest nurseries as effective growth stimulators at cultivation of Siberian spruce landing material.